Halloween cupcake murder - O'Connor, Carlene; Ireland, Liz; Perry, Carol J. (Waterville, ME Thorndike Press, 2023)
"In Halloween Cupcake Murder by Carlene O'Connor, Tara Meehan finds herself tangled in a mystery with ancient Gaelic roots, but very modern - and very deadly - consequences. In Mrs. Claus and the Candy Corn Caper by Liz Ireland, tragedy strikes at Santaland's newest bakery. The only clue is a cupcake, leaving Mrs. Claus to sort through tricks and treats as she races to unmask a Halloween fiend. In A Triple Layer Halloween Murder by Carol J. Perry, rumors swirl after a wealthy bakery owner goes missing. Now, Lee must conjure clues to reveal the missing millionaire . . . or the truth about his disappearance" --
Halloween cupcake murder / Carlene O'Connor -- Mrs. Claus and the candy corn caper / Liz Ireland -- A triple layer Halloween murder / Carol J. Perry.
Includes a recipe
113345
Keywords: Bakeries -- Fiction; Bakers -- Fiction; Festivals -- Fiction; Halloween -- Fiction; Murder -- Fiction; Large type books; Fiction -- Mystery & Detective -- Collections & Anthologies; Large type books; Detective and mystery fiction; Novellas